PROVISION OF MEDICAL SERVICES IN FERGANA VALLEY - Qodirjon Najmiddinov (American Journals Publishing, 2023)
This article covers the daily life of the residents of Andijan, Fergana and Namangan regions of the Republic of Uzbekistan in the 1960s-1980s and the state of medical services. Also, the works performed on the health of the population and their provision are also included in this article.
Keywords: Poliomyelitis, gout, measles, tuberculosis, meningococcus, typhoid fever, paratyphoid, diphtheria, smallpox.